2020
DOI: 10.1002/jbmr.4468
|View full text |Cite
|
Sign up to set email alerts
|

The Glucocorticoid Receptor in Osterix-Expressing Cells Regulates Bone Mass, Bone Marrow Adipose Tissue, and Systemic Metabolism in Female Mice During Aging

Abstract: Hallmarks of aging‐associated osteoporosis include bone loss, bone marrow adipose tissue (BMAT) expansion, and impaired osteoblast function. Endogenous glucocorticoid levels increase with age, and elevated glucocorticoid signaling, associated with chronic stress and dysregulated metabolism, can have a deleterious effect on bone mass. Canonical glucocorticoid signaling through the glucocorticoid receptor (GR) was recently investigated as a mediator of osteoporosis during the stress of chronic caloric restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Contrary to estrogens, the steroid hormone cortisol can upregulate BMA. Cortisol and glucocorticoid receptor knock-out have been associated with higher BMA 58 . In our cohort, morning cortisol levels increased in both sexes during spaceflight and rapidly returned to baseline postflight (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Contrary to estrogens, the steroid hormone cortisol can upregulate BMA. Cortisol and glucocorticoid receptor knock-out have been associated with higher BMA 58 . In our cohort, morning cortisol levels increased in both sexes during spaceflight and rapidly returned to baseline postflight (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the unexpected finding of a fat phenotype driven by Osx-Cre , we also did not anticipate the strong effect of age on activation of this Cre . Previous studies utilizing this Cre driver primarily utilize mice under 6 months of age, and the few studies with mice at or beyond 1 year of age did not describe, or specifically look for, Cre expression outside of bone 39 41 . Since this study was undertaken to examine the role of IKKα in bone, studies of fat and metabolism were not initially planned.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Osterix can promote mitochondrial biogenesis and function in osteoblasts ( Shahi et al, 2017 ). It does so by activating the expression of genes involved in oxidative phosphorylation and mitochondrial respiration, which results in increased ATP production and enhanced cellular metabolism ( Pierce et al, 2022 ). Osterix also regulates the expression of genes involved in glucose metabolism, including GLUT1, a glucose transporter that facilitates glucose uptake and utilization in osteoblasts ( Kong et al, 2021 ).…”
Section: Cell Metabolic Regulation In Bone Regenerationmentioning
confidence: 99%